Penggunaan Eufemisme dalam Komentar di Postingan Akun Instagram Akun @nadiemmakarim - Yosani, Yosephine Marrietta Ardhya; Ginanjar, Bakdal; Nurjanah, Ayu Fitria (Hasta Wiyata, 2022)
Social media is an application that humans can use to communicate, one of which is Instagram. In communicating, the language used is polite language or contains euphemisms so as not to cause misunderstandings with the interlocutor. In this study, research was conducted on the types of euphemisms contained in the comments on the Instagram account @nadiemmakarim. The purpose of this study is to describe the types of euphemisms contained in the comments of the Instagram account @nadiemmakarim. This research is in the form of a qualitative descriptive with the data source of the Instagram account @nadiemmakarim. The data is in the form of 35 comments and analyzed using the agih method and the dressing technique. The results of this study found that there are figurative euphemisms, clipping euphemisms, acronym euphemism, one word euphemisms to replace another word, and jargon euphemisms. The most dominant type of euphemism is one word euphemism to replace another word with the function og softening the word so as not to offend the interlocutor.